Characteristics of Cohesin Mutation in Acute Myeloid Leukemia and Its Clinical Significance - Han, Caixia; Gao, Xuefeng; Li, Yonghui; Zhang, Juan; Yang, Erna; Zhang, Li; Yu, Li (Frontiers in Oncology, 2021)
The occurrence of gene mutation is a major contributor to the initiation and propagation of acute myeloid leukemia (AML). Accumulating evidence suggests that genes encoding cohesin subunits have a high prevalence of mutations in AML, especially in the t(8;21) subtype. Therefore, it is important to understand how cohesin mutations contribute to leukemogenesis. However, the fundamental understanding of cohesin mutation in clonal expansion and myeloid transformation in hematopoietic cells remains ambiguous. Previous studies briefly introduced the cohesin mutation in AML; however, an in-depth summary of mutations in AML was not provided, and the correlation between cohesin and AML1-ETO in t (8;21) AML was also not analyzed. By summarizing the major findings regarding the cohesin mutation in AML, this review aims to define the characteristics of the cohesin complex mutation, identify its relationships with co-occurring gene mutations, assess its roles in clonal evolution, and discuss its potential for the prognosis of AML. In particular, we focus on the function of cohesin mutations in RUNX1-RUNX1T1 fusion.